Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Sembako Pada PT Sinar Setia di Bandar Lampung - Kurniawan, Sandy Frans; Patmarina, Hepiana (Jurnal EMT KITA, 2024)
Understanding consumer behavior plays a crucial role in formulating marketing strategies to meet the needs and desires of customers, ultimately enhancing customer satisfaction. This research aims to investigate the influence of consumer behavior (X1) on purchasing decisions (Y) of groceries at PT Sinar Setia, located at Jl. Sultan Hasanudin No. 60A, Bandar Lampung. This study was chosen because a deep understanding of consumer behavior can provide valuable insights into analyzing consumer preferences and habits, which are essential for businesses to optimize their marketing strategies. This study employs a quantitative research approach with primary data obtained directly from the research object. Data were collected through the distribution of questionnaires and observation at PT Sinar Setia. A Likert scale was used to measure respondents' responses, with scores ranging from 1 to 5. The total population of respondents was 480, with a sample of 83 respondents selected through accidental sampling technique. Data analysis was conducted using simple linear regression and SPSS statistical software. The research findings indicate that the t-value of 5.813 exceeds the t-table value of 1.9896, with a significance value of 0.000 < 0.05, demonstrating that the consumer behavior variable (X1) significantly influences purchasing decisions (Y).